2012
DOI: 10.1063/1.4737580
|View full text |Cite
|
Sign up to set email alerts
|

Zonal flows in stellarators in an ambient radial electric field

Abstract: The linear dynamics of zonal flows is addressed in stellarator geometry in the presence of an ambient (neoclassical) radial electric field. Global gyrokinetic particle-in-cell simulations are used to study the properties of the residual flow and its dependence on the plasma parameters and magnetic geometry. Properties of the zonal flow are compared in different magnetic geometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…The maximum is reached for times around t = 0, the time at which the neoclassical electric field is close to zero at those radial locations. Finite orbit widths effects of the ambient E r are expected to enhance the damping of the LFO in helical systems [34] in consistency with previous simulations [35] for the TJ-II geometry. The maximum amplitude time delay observed for the different radial locations in figure 9 is due to the inward propagation of the region of small radial electric field associated to electron-to-ion root jump described in previous sections.…”
Section: Gyrokinetic Simulations Of Zonal Flow Relaxation During the supporting
confidence: 90%
“…The maximum is reached for times around t = 0, the time at which the neoclassical electric field is close to zero at those radial locations. Finite orbit widths effects of the ambient E r are expected to enhance the damping of the LFO in helical systems [34] in consistency with previous simulations [35] for the TJ-II geometry. The maximum amplitude time delay observed for the different radial locations in figure 9 is due to the inward propagation of the region of small radial electric field associated to electron-to-ion root jump described in previous sections.…”
Section: Gyrokinetic Simulations Of Zonal Flow Relaxation During the supporting
confidence: 90%
“…The amplification of low frequency ZF-structures in plasma scenarios with reduced Neoclassical viscosity has been observed in TJ-II [138]. In addition, gyrokinetic simulations have shown that radial electric fields may affect the residual level of zonal flows in stellarators [139,140]. Experiments performed in the TJ-II stellarator have shown that long range correlations detected in potential fluctuations, consistent with zonal flows, are amplified either by externally imposed radial electric fields or when approaching the L-H confinement edge transition.…”
Section: Zonal Flows and Radial Electric Fieldsmentioning
confidence: 93%
“…A background long-wavelength radial electric field is known to have an effect on both the residual ZF level (Sugama & Watanabe 2009) and also on its oscillation frequency (Mishchenko & Kleiber 2012); then, it is worth checking the effect of using these NCST tools on the ZF evolution with a background electric field included in the simulation. The results of this test for two values of the background electric field are shown in figures 11 and 12.…”
Section: Characterization Of Ncstsmentioning
confidence: 99%
“…Influence of the Krook operator (a), heating source, γ h , (b) and weight smoothing, σ QT (with N QT = 10, f QT = Ω * ) (c), on the linear evolution of the zonal potential component in W7-X equilibrium for different values of parameters including an electric field dφ/dr = r/a 2 . Influence of the Krook operator (a), heating source, γ h , (b) and weight smoothing, σ QT (with N QT = 10, f QT = Ω * ) (c), on the linear evolution of the zonal potential component in a W7-X equilibrium for different values of parameters including an electric field dφ/dr = 2r/a 2 (Mishchenko & Kleiber 2012)…”
mentioning
confidence: 99%